Robots in education : an introduction to high-tech social agents, intelligent tutors, and curricular tools /: an introduction to high-tech social agents, intelligent tutors, and curricular tools. (2021) - Alnajjar, Fady; Bartneck, Christoph; Baxter, Paul; Belpaeme, Tony; Cappuccio, Massimiliano; Di Dio, Cinzia; Eyssel, Friederike; Handke, Jürgen; Mubin, Omar; Obaid, Mohammad; Reich-Stiebert, Natalia
No abstract available